Codzienność i refleksja. W poszukiwaniu źródeł uczenia się osób dorosłych - Frąckowiak, Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In the paper the issue of factors and conditions constituting adult learning is discussed. The author aims at answering questions, such as – what starts the process of learning in daily life situations, what situations may be educative for adults in daily life, what is the meaning of reflexion in experiencing daily life and the process of learning from it. She pays special attention to constituencies of daily life situations, which run the process of adult learning as well as make adult more reflexive. In the end she also highlights results of reflexion in adult life, and conditions underlying using reflexion outcomes or lack of it.
Keywords: adult learning; daily life; experiencing reality; fenomenology; reflextion